Comparison of a fungal and a bacterial laccase for lignosulfonate polymerization. (October 2021) - Braunschmid, Verena; Binder, Karin; Fuerst, Sarah; Subagia, Raditya; Danner, Caroline; Weber, Hedda; Schwaiger, Nikolaus; Nyanhongo, Gibson S.; Ribitsch, Doris; Guebitz, Georg M.
Graphical abstract: Highlights: Heterologous expression of laccase Ma L1 from Melanocarpus albomyces in P.pastoris . Almost two-fold increase of the molecular weight of lignosulfonate after polymerisation with Ma L1. No mediator needed for polymerization of lignosulfonate. Abstract: Lignin is the second most abundant biopolymer on earth and accrues in large amounts in the pulp- and paper industry. While currently lignins are mainly used for low-value applications such as energy production, recently the potential of laccases for upgrading lignins has been demonstrated. In this study, two laccases of fungal and bacterial origin were characterized regarding their potential to polymerize lignosulfonate. The laccases Ma L1 from Melanocarpus albomyces, and Sr LA from Streptomyces rochei were heterologously expressed and showed typical characteristics of laccases, like acidic pH optima for ABTS at pH 4 and 5, respectively, and temperature optima at 50 °C and 80 °C. Polymerization of lignosulfonate with Ma L1 led to an almost two-fold increase of the molecular weight, according to size exclusion (SEC) multiangle laser light scattering (MALLS) analysis. In contrast, Sr LA showed considerably less activity on lignosulfonates, as measured based on oxygen consumption and SEC-MALLS.